Relationships between Ca/K plasma ratio and parameters of heart rate variability at patients with diathesis urica - Oleksandra I. Fajda; Oleksandr V. Drach; Liliya G. Barylyak; Walery Zukow (Kazimierz Wielki University, 2016)
Fajda Oleksandra I., Drach Oleksandr V., Barylyak Liliya G., Zukow Walery. Relationships between Ca/K plasma ratio and parameters of heart rate variability at patients with diathesis urica. Journal of Education, Health and Sport. 2016;6(1):295-301. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45359 http://ojs.ukw.edu.pl/index.php/johs/article/view/3368 https://pbn.nauka.gov.pl/works/710817       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. RELATIONSHIPS BETWEEN Ca/K PLASMA RATIO AND PARAMETERS OF HEART RATE VARIABILITY AT PATIENTS WITH DIATHESIS URICA   Oleksandra I. Fajda1, Oleksandr V. Drach2, Liliya G. Barylyak2,3, Walery Zukow4   1JSC "Dnipro-Beskyd", Truskavets', Ukraine    alexavka7@gmail.com 2JSC " Truskavets'kurort", Truskavets', Ukraine   lgbarylyak@gmail.com 3Laboratory of Experimental Balneology, OO Bohomolets' Institute of Physiology NAS, Truskavets'-Kyiv, Ukraine     i.popovych@ukr.net 4Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   w.zukow@ukw.edu.pl   Abstracts Background. Previously we shown that Kerdö's Vegetative Index is not marker of sympatho-vagal balance, but reflects above all Amplitude of α-Rhythm EEG and its Power Spectrum Density in Parietal and Central loci, less options HRV. The aim of present study is analyze the relationships other marker of sympatho-vagal balance Ca/K Plasma Ratio with parameters of HRV. Methods. In basal conditions in twentee volunteers - ten women add ten men aged 33-76 years with diathesis urica recorded Heart Rate Vatiability (HRV) ("Cardiolab+VSR", KhAI Medica, Ukraine). In blood plasma measured the concentration of Calcium and Potassium. Results. No correlation ascertained between Ca/K Plasma Ratio and LF/HF Ratio (r=-0,07) and LFnu (r=0,09). However, Ca/K Plasma Ratio moderately negatively correlated with vagal markers: SDNN (r=-0,30), RMSSD (r=-0,34), pNN50 (r=-0,36), HRV TI (r=-0,34), absolute PS HF (r=-0,33) and positively with sympathetic marker Amplitude of Moda (r=0,24 for actual values and 0,38 for portion of age norm) as well as with relative PS ULF (r=0,39). The strongest correlations of Ca/K Plasma Ratio proved with absolute PS LF (r=-0,45) and variational sweep: r=-0,42 for actual values and -0,49 for portion of age norm. Canonical correlation between Ca/K Plasma Ratio, on the one hand, and the parameters of HRV, on the other hand, is strong: R=0,713; R2=0,509; Adjusted R2=0,437; F(5,3)=7,0; χ2(5)=25,2; p=10-4. Conclusion. Ca/K Plasma Ratio reflects inversely vagal tone and less direct sympathetic tone, therefore is really marker of sympatho-vagal balance.   Keywords: Ca/K Plasma Ratio, HRV, correlations.